The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/ina.12756
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term exposure to indoor air pollution and risk of tuberculosis

Abstract: Tuberculosis (TB), caused by mycobacterium tuberculosis (M tb), is the second most prevalent infectious disease 1,2 and accounts for about 1.5 million deaths annually. 3 Low-and middle-income countries (LMIC) bear disproportionately higher burden of TB mortality and morbidity. 4 Among LMIC, India has the highest incidence and prevalence rates of TB in the world. 5 Many factors are shown to increase the risk of activation from latent TB infection to clinically manifested active TB and its severity, including h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…In addition, exposure to air pollution, both indoor and outdoor, is a potential contributing factor to the TB epidemic (Lin et al 2007;Popovic et al 2019). Some studies have revealed associations between TB cases and indoor air pollution, primarily due to the inhalation of environmental pollutants such as tobacco smoke and biomass fuel smoke (Jafta et al 2019;Patel et al 2020). In recent years, the association between ambient air pollution and TB risk has received constant attention from scholars (Ge et al 2017;Lai et al 2016;Li et al 2019;Smith et al 2016;Sohn et al 2019;Zhu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, exposure to air pollution, both indoor and outdoor, is a potential contributing factor to the TB epidemic (Lin et al 2007;Popovic et al 2019). Some studies have revealed associations between TB cases and indoor air pollution, primarily due to the inhalation of environmental pollutants such as tobacco smoke and biomass fuel smoke (Jafta et al 2019;Patel et al 2020). In recent years, the association between ambient air pollution and TB risk has received constant attention from scholars (Ge et al 2017;Lai et al 2016;Li et al 2019;Smith et al 2016;Sohn et al 2019;Zhu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The combustion of solid fuels emits many chemicals which impact human health, including PM, carbon dioxide, carbon monoxide, sulfur dioxide (SO 2 ), sulfur trioxide, nitrogen dioxide, and nitric oxide [ 29 ]. There is increasing evidence that PM exposure weakens anti-mycobacterial host immunity [ 30 , 31 ]. Chronic PM exposure accompanied by high constitutive expression of pro-inflammatory cytokines results in relative cellular unresponsiveness [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“… 22 Indoor air pollution has shown to be an important predisposing and enabling factor for tuberculosis. 23 , 24 Usage of unclean cooking fuel which is rampant in developing countries is one of the important causes globally for indoor air pollution. 25 , 26 This study also supports this finding.…”
Section: Discussionmentioning
confidence: 99%